FIGURATIVE LANGUAGE ANALYSIS IN CELINE DION’S SONG LYRICS FALLING INTO YOU ALBUM - Stella Vania Ardhyanti; Supriyatiningsih Supriyatiningsih (PROJECT (Professional Journal of English Education), 2020)
Figurative language is the ways to show the writer’s thought use the special word, which have hidden meaning of it. This research analyzed Celine Dion’s songs, they are Fly and Falling into You. The objectives of this research are to find out the types of figurative language and meanings of the figurative language in Celine Dion’s songs. The writers take two songs from this album, they are Fly and Falling into You. The method of this research was qualitative descriptive. The data were taken from Genius.com website. Figurative language that the writers found in this research were six metaphors, two symbolisms, two imageries, two similes and one personification. In the Fly song there were four metaphors, and one symbolism. Besides in the Falling into You song there were two metaphors, one symbolism, two imageries, two similes, and one personification. The writers found the hidden meaning of these two songs. The Fly song told about parents who express deep sadness at the loss of her child. While, the Falling into You song told about someone who show his/her felling to someone they loved.Keywords:     Figurative Language, Song Lyrics, Contextual Meaning